Microcephaly and Zika virus: a clinical and epidemiological analysis of the current outbreak in Brazil - Nunes, Magda Lahorgue; Carlini, Celia Regina; Marinowic, Daniel; Neto, Felipe Kalil; Fiori, Humberto Holmer; Scotta, Marcelo Comerlato; Zanella, Pedro Luis Ávila; Soder, Ricardo Bernardi; da Costa, Jaderson Costa (Jornal de pediatria, 2016)
This study aimed to critically review the literature available regarding the Zika virus outbreak in Brazil and its possible association with microcephaly cases. Experts from Instituto do Cérebro do Rio Grande do Sul performed a critical (nonsystematic) literature review regarding different aspects of the Zika virus outbreak in Brazil, such as transmission, epidemiology, diagnostic criteria, and its possible association with the increase of microcephaly reports. The PubMed search using the key word “Zika virus” in February 2016 yielded 151 articles. The manuscripts were reviewed, as well as all publications/guidelines from the Brazilian Ministry of Health, World Health Organization and Centers for Disease Control and Prevention (CDC – United States). Epidemiological data suggest a temporal association between the increased number of microcephaly notifications in Brazil and outbreak of Zika virus, primarily in the Brazil's Northeast. It has been previously documented that many different viruses might cause congenital acquired microcephaly. Still there is no consensus on the best curve to measure cephalic circumference, specifically in preterm neonates. Conflicting opinions regarding the diagnosis of microcephaly (below 2 or 3 standard deviations) that should be used for the notifications were also found in the literature. The development of diagnostic techniques that confirm a cause–effect association and studies regarding the physiopathology of the central nervous system impairment should be prioritized. It is also necessary to strictly define the criteria for the diagnosis of microcephaly to identify cases that should undergo an etiological investigation. O objetivo deste estudo foi realizar uma revisão crítica da literatura sobre o surto de vírus Zika no Brasil e sua possível associação com casos de microcefalia. Especialistas em áreas afins do Instituto do Cérebro do Rio Grande do Sul realizaram uma revisão crítica (não sistemática) da literatura sobre o vírus Zika, suas formas de transmissão, a epidemia no Brasil, critérios diagnósticos e a possível associação com os casos crescentes de microcefalia. O uso da palavra chave “Zika virus” na base de dados do PubMed em fevereiro de 2016, retorna 151 publicações. Estes textos foram revisados assim como todas as publicações e recomendações do Ministério da Saúde, Organização Mundial da Saúde e Centro de Controle de Doenças (CDC – USA). Os dados epidemiológicos sugerem uma relação temporal entre aumento da notificação de casos de microcefalia e o surto de vírus Zika, principalmente no Nordeste do Brasil. Agentes virais comprovadamente podem ser causadores de microcefalia congênita adquirida. Não existe um consenso sobre a melhor curva de perímetro cefálico a ser utilizada, principalmente nos prematuros. Assim como também existem divergências sobre a definição de microcefalia (abaixo de 2 ou 3 desvios padrões) a ser padronizada nas notificações. Deve-se priorizar o desenvolvimento de técnicas diagnósticas que confirmem uma relação causa–efeito e estudos sobre mecanismos da patogênese da infecção pelo Zika no sistema nervoso central. Também é necessário definir e universalizar os critérios diagnósticos para a identificação dos casos de microcefalia que devem ser submetidos à investigação etiológica.